Remineralization of Artificial Caries in Primary Teeth by Grape Seed Extract: An In Vitro Study - Mahkameh Mirkarimi (Journal of Dental Research, Dental Clinics, Dental Prospects, 2013)
Background and aims. Promoting remineralization is the ultimate goal of clinical prevention of caries lesion. The present in vitro study aimed to investigate the effect of grape seed extract (GSE) on artificial enamel caries in primary human teeth. Materials and methods. Seventeen human sound primary incisors were sectioned mesiodistally. The tooth slices were placed in a demineralizing solution for 96 hours at 37ºC and 50% relative humidity to create lesions. The demineralized fragments of each tooth were randomly divided into two case (immersed in GSE solution in phosphate buffer for 8 days) and control (immersed in distilled water) groups. The samples were subsequently evaluated using a scanning electron microscope and a micro-hardness tester. Data were analyzed using independent t-test. Results. The mean ± SD micro-hardness values for the case and control groups were 358.6±83.42 and 296.51± 69.41, respectively. Grape seed extract significantly increased the micro-hardness of the lesions (P=0.03). The morphology of GSE treated enamel was clearly different from that in the control group, and there were deposits of scaffolding insoluble complexes on the enamel surface. Conclusion. GSE enhanced the remineralization process of artificial enamel lesions of primary teeth, and thus, might be considered an effective natural agent in non-invasive dentistry.